2018
DOI: 10.18089/tms.2018.14304
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology & tourism: a systematic literature review

Abstract: This study aims to outline the relationship between Positive Psychology and tourism through a systematic literature review. Tourism seeks to increase the wellbeing of people, and wellbeing is a crucial variable in Positive Psychology which in turn aims to understand and promote people's potential. This research used as search terms 'Positive Psychology', 'wellbeing', 'happiness', 'tourism', 'visitor' and 'travel', terms which were applied through the Online Knowledge Library. The inclusion/exclusion criteria l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
1
34
0
3
Order By: Relevance
“…Growing attention has been devoted to the psychological impacts of tourism experiences on travelers' well‐being and quality of life (Dolnicar, Yanamandram, & Cliff, 2012; Filep, 2012; Uysal, Sirgy, Woo, & Kim, 2016). A systematic review of previous literature provides substantial empirical evidence to support the positive impact of tourism activities on tourists' perceptions of well‐being (Chen & Petrick, 2013; Garcês, Pocinho, Jesus, & Rieber, 2018). Well‐being is conceptualized as a multidimensional domain of quality of life, often associated with various psychological, material, and physical dimensions (Dolnicar et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing attention has been devoted to the psychological impacts of tourism experiences on travelers' well‐being and quality of life (Dolnicar, Yanamandram, & Cliff, 2012; Filep, 2012; Uysal, Sirgy, Woo, & Kim, 2016). A systematic review of previous literature provides substantial empirical evidence to support the positive impact of tourism activities on tourists' perceptions of well‐being (Chen & Petrick, 2013; Garcês, Pocinho, Jesus, & Rieber, 2018). Well‐being is conceptualized as a multidimensional domain of quality of life, often associated with various psychological, material, and physical dimensions (Dolnicar et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found PERMA as a valuable tool for gaining an in‐depth understanding of tourists' perceptions of well‐being. In a recent review of positive psychology literature in tourism, Garcês et al (2018) found that the individual well‐being effects resulting from tourism experiences closely correspond with the multiple dimensions of PERMA. Dillette, Douglas, and Martin (2018) used PERMA to capture tourists' sense of well‐being associated with wellness tourism experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive Psychology has a broad scope and a multidisciplinary view that allies' researches from multiple fields (Titus, 2017), hence its endeavours can clearly extend to tourism settings. In a systematic literature review, linking Positive Psychology and Tourism (Garcês, Pocinho, Jesus, & Rieber, 2018), results showed that tourism is seen as a way to promote wellbeing for host communities and tourists. Also, in the same study, it was found that wellbeing can be understood as an opportunity for businesses innovation and that it is deeply related to nature.…”
Section: Discussionmentioning
confidence: 99%
“…de (2017) evdeki boş zaman aktivitelerine kıyasla seyahat sırasında insanların öznel iyi oluşunun daha yüksek, ruminatif düşüncenin daha az olduğunu ölçümlemiştir. Garcês vd. (2018) sosyal bilimler alanındaki çeşitli veri tabanlarında pozitif psikoloji, iyi oluş, mutluluk, turizm, ziyaretçi, seyahat kavramlarını taratarak 2007 ve 2017 yılları arasında pozitif psikoloji ve turizmi birlike ele alan literarürü taramış ve ulaştıkları 49 makaleye meta-analiz uygulamışlardır.…”
Section: Pozitif Psikoloji Ve Turizmunclassified
“…Araştırmacılar yeni bilgi edinme arzusunda olan ve yeni deneyimler arayan bir gezgin dalgasının büyüdüğüne işaret etmektedir. Garcês vd. (2018) günümüzde bireysel gelişim ve kendini gerçekleştirmeye odaklanan yeni bir "deneyim ekonomisi" fikrinin yükselişine şahitlik edildiğini belirtmektedir.…”
Section: Pozitif Psikoloji Ve Turizmunclassified